Upaya Meningkatkan Karakter Disiplin Anak Melalui Pohon Kedisiplinan di Tk IK Keluarga Ceria Sleman - Rizqiyyatunnisa Rizqiyyatunnisa (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2020)
The background of the problem in this study is that the behavior of the discipline is not fully owned by the children, so that it affects the teaching and learning process in the classroom. There needs to be a renewal in the form of strategies or media that can familiarize the discipline behavior of children, so that children can get used to discipline by using the discipline tree. This study aims to determine the application of the